2022
DOI: 10.1186/s12871-022-01568-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delta-opioid receptor agonist pretreatment on the cardiotoxicity of bupivacaine in rats

Abstract: Background Delta-opioid receptor is widely expressed in human and rodent hearts, and has been proved to protect cardiomyocytes against ischemia/reperfusion and heart failure. The antagonist of delta-opioid receptor could block the rescue effect of lipid emulsion against local anesthetic cardiotoxicity. However, no evidence is available for the direct effect of delta-opioid-receptor agonists on the cardiotoxicity of local anesthetics. Methods Anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Opioid receptors are mainly categorized into κ (KOR), µ (MOR), and δ (DOR) subtypes, all of which belong to G protein-coupled receptors. DORs are widely distributed in the central nervous system, peripheral nervous system and the cardiovascular system [ 14 ]. In our previous study, we found that DADLE, a synthetic DOR agonist, played a protective role in cerebral and spinal cord I/R injury [ 9 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Opioid receptors are mainly categorized into κ (KOR), µ (MOR), and δ (DOR) subtypes, all of which belong to G protein-coupled receptors. DORs are widely distributed in the central nervous system, peripheral nervous system and the cardiovascular system [ 14 ]. In our previous study, we found that DADLE, a synthetic DOR agonist, played a protective role in cerebral and spinal cord I/R injury [ 9 , 15 ].…”
Section: Discussionmentioning
confidence: 99%